Characterization of suicidal behavior in the Province of Villa Clara - Dairon Vázquez Ramos; Ariel Arango Díaz; Yunior Jesús Pacheco Fuentes; Edel Castellanos Sánchez; Yadira Janet Sierra Ruíz; Milagros Caridad Ruíz Ramos (Acta Médica del Centro)
Introduction: suicidal behavior is a health problem that results in a high risk for the physical and psychological integrity of the individual. Objective: to characterize suicidal behavior in the Province of Villa Clara in the period from January 2016 to December 2020. Methods: an observational, descriptive, cross-sectional study was carried out. 5,700 patients who had suicidal behavior in the province during the period studied were studied. To obtain the necessary information, the notifiable disease cards were reviewed. The quantitative variables were described using absolute frequencies, relative frequencies and rates. Results: the year 2016 showed a higher incidence of suicide attempts, with a rate of 160x100 000 inhabitants. The mortality rate from suicide was higher in males and in patients 80 years of age and older, including both sexes. Suicide attempts were recorded at a higher rate in female patients between 25 and 59 years old. The highest rate per 100,000 inhabitants of suicide attempts was recorded in the Municipality of Camajuaní (163.6) and the highest mortality rate due to suicide in the Municipality of Corralillo (29.4). Conclusions: more than half of those who died by suicide had premature mortality and the rate of years of potential life lost was lower than the national rate. The municipalities with the highest mortality from suicide and the highest mortality from suicide attempts were those with the greatest number of rural areas.